PENERAPAN ILMU EKONOMI TEKNIK DALAM MENGANALISA KELAYAKAN FINANSIAL USAHA BAGI SISWA SMKN 1 SITUBONDO - Melina, Nabila; Maudiani, Moh.; Haykal, Muhammad; Milya, Abidah; Ahmad, R. Sultan; Shelina, Dyan; Diana, Feriska; Andreanto, Erwan; Zhulfikar, Muhammad; Gunasti, Amri (Jurnal Abdi Insani, 2024)
Engineering economics is a discipline that combines economic principles with engineering analysis to evaluate the financial feasibility of projects and investments. At SMKN 1 Situbondo, the application of this knowledge is important in order to improve the financial analysis skills of students and school administrators. Vocational education requires a more practical and applicable approach, especially in the context of business development and projects that require initial investment. This service aims to apply technical economics in analyzing the financial feasibility of businesses at SMKN 1 Situbondo, with the main focus on increasing the competence of students and school managers in understanding and applying technical economics concepts in the context of business and entrepreneurship. Implementation of this activity begins with observation to determine the goal of the school where this service activity is to be held, from the results of the observation we determine which SMKN 1 Situbondo is the goal of this service activity, followed by a survey as well as coordination with teaching staff and submitting a permission letter from the campus for service activities, followed by counseling which contains material presentations, discussions and questions and answers, as well as training in Excel calculations to assess the feasibility of a business, finally we conduct an evaluation of the service activities that have been carried out. Overall, this service not only succeeded in improving technical skills in financial analysis but also had a positive impact on students' readiness to face the challenges of the business world. These results show that the application of technical economics at SMKN 1 Situbondo has been successful and provides sustainable benefits for the school community. This service shows that the application of technical economics at SMKN 1 Situbondo has succeeded in improving the quality of vocational education, preparing students for the challenges of the business world, and making a positive contribution to local economic development. These results emphasize the importance of integrating engineering economics in the vocational education curriculum and the need for ongoing support for the development of the competencies of students and school administrators